Optimization and Scheduling Strategy for Regional Multi-dimensional Charging of Electric Vehicles Based on Compensation Mechanism - Jianhua YUAN; Tianyu ZHANG; Guangsheng CHEN; Tao HUANG (Zhongguo dianli)
To improve the power supply service provider’s economic efficiency and user’s satisfaction under the background of electric vehicle (EV) charging-disorder in varied charging settings, this paper proposes a compensation-based optimization and scheduling strategy for regional multi-dimensional charging of electric vehicles. Firstly, clusters are formed based on energy consumption patterns and temporal flexibility, and a compensation perception model is established based on charging compensation and time pressure. A user satisfaction model and a regret theory-based user charging decision model are developed with consideration of charging cost, time and quantity of users. And then, a daily rolling energy replenishment model is established for batteries at BCSS. Finally, an optimization scheduling model is created to optimize the charging compensation for maximizing the provider’s revenue and minimizing the regional consumption imbalances. The proposed strategy, verified through Matlab simulation, boosts the power supply service provider’s revenue and slashs the regional consumption deviation, while maintaining the user’s satisfaction with the charging solution.